Physicochemical and microbiological characteristics of yogurt from encapsulated beetroot (Beta vulgaris L.) coloring (@limentech, Ciencia y Tecnología Alimentaria, 2015)
The objective of this work was to encapsulate beetroot coloring by the extrusion method and determine its effect on the addition of yogurt.For this experiment, coloring extracted from beetroot was used and encapsulated. A batch of yogurt was prepared to be divided into two treatments, to the first 0.6% of capsules containing the coloring to be encapsulated in 2% sodium alginate was added, to the second treatment no capsules were added. Statistically, it was found that there were no significant differences in the two treatments for pH and acidity; opposite occurred with syneresis, showing significant differences. The encapsulation technique used, such as extrusion for the colorant, was viable for 9 days during yogurt storage; the pH, acidity, and lactic acid bacteria count behaved similarly to yogurt without capsules.
Keywords: Color; encapsulation; yogurt